Goldenhar syndrome and hemifacial microsomia. A literature review - Cazenave, Lissette (2017)
Hemifacial microsomia is the second congenital malformation in prevalence, after cleft lip and palate, and is described as a congenital alteration of the first and second branchial arches. Goldenhar syndrome has typical characteristics of hemifacial microsomia with the addition of epibulbar dermoids and vertebral anomalies. Both pathologies have variable expression’s characteristics and therefore the treatments are according to their individuality. In this review of the topic is analyzed the etiology, classifications, characteristics and treatment.